Direct and indirect effects of the fungal endophyte Epichloë uncinatum on litter decomposition of the host grass, Schedonorus pratensis - Gundel, Pedro Emilio (2017)
Microbial plant symbionts have been suggested to mediate plant-soil feedback and affect ecosystem functions. Systemic Epichloë fungal endophytes of grasses are found to mediate litter decomposition. These effects are often linked to alkaloids produced by Epichloë species, which are hypothesized to negatively affect decomposers. Although endophytes have been found to affect plant community and soil biota, direct (through litter quality) and indirect (through the environment) effects of fungal endophytes on litter decomposition have been scarcely scrutinized. We placed litterbags with endophyte-symbiotic (E+) and non-symbiotic (E−) Schedonorus pratensis plant litter in plots dominated by E+ or E− plants of the same species, and followed the dynamics of mass losses over time. We predicted the endophyte would hinder decomposition through changes in litter quality and that both types of litter would decompose faster in home environments. E+ litter decomposed faster in both environments. The mean difference between decomposition rate of E+ and E− litter tended to be higher in E− plots. Nitrogen and phosphorus, two elements usually associated with high decomposition rates, were significantly lower in E+ litter. We also detected a higher proportion of C in the cellulose form in E+ litter. Contrary to the general assumption, we found that symbiosis with Epichloë fungal endophytes can be associated with higher decomposition of plant litter. Since direct effects of Epichloë fungi were still stronger than indirect effects, it is suggested that besides the alkaloids, other changes in plant biomass would explain in a context-dependent manner, the endophyte effects on the litter decomposition.